Ablutionary Urbanisms: Water Infrastructures, Cultural Production and Charitable Dispensation - Muller, Brook (Frontiers in Water, 2022)
With interest in advancing inclusive urban landscapes and guided by principles of social and cultural sustainability, this essay speculates as to localized water infrastructures as “ablutionary urbanisms,” important forms of contemporary design expression in a context of rapid growth, widening inequalities, climate change and lack of resilience. It derives inspiration from vernacular precedents in advocating for an integrated, decentralized approach to addressing current urban water challenges. It explores the contemporary relevance of the sabil, a prominent civic feature of Islamic cities intended for the charitable dispensation of water. More specifically, this essay considers the contemporary relevance and potency of the sabil-kuttab, a hybrid building type unique to the city of Cairo in which a school (kuttab) sits atop a sabil. Such a type offers helpful guidance in devising principles and precepts relevant to contemporary infrastructural design in that: (1) it offers encouragement to advocate for distributed urban water systems as civically prominent elements of cities, particularly as these systems combine with other important community-focused programmatic features; and (2) given a reimagining of urban water systems as critical forms of cultural production, it offers encouragement for interdisciplinary teams to commit to the task of infrastructure planning as a promising locus of integrative design.